Predictive Potential of Flow Cytometry Crossmatching in Deceased Donor Kidney Transplant Recipients Subjected to Peritransplant Desensitization - Osickova, Klara; Hruba, Petra; Kabrtova, Katerina; Klema, Jiri; Maluskova, Jana; Slavcev, Antonij; Slatinska, Janka; Marada, Tomas; Böhmig, Georg A.; Viklicky, Ondrej (Frontiers in Medicine, 2021)
Recipient sensitization is a major risk factor of antibody-mediated rejection (ABMR) and inferior graft survival. The predictive effect of solid phase HLA antibody testing and flow cytometry crossmatch in the era of peritransplant desensitization remains poorly understood. This observational retrospective single-center study with 108 donor-specific antibody (DSA)-positive deceased donor kidney allograft recipients who had undergone peritransplant desensitization aimed to analyze variables affecting graft outcome. ABMR rates were highest among patients with positive pretransplant flow cytometry crossmatch (FCXM) vs. FCXM-negative (76 vs 18.7%, p<0.001) and with DSA MFI > 5000 vs. <5000 (54.5 vs 28%, p=0.01) despite desensitization. In univariable Cox regression, FCXM positivity, retransplantation, recipient gender, immunodominant DSA MFI, DSA number and peak PRA were found to associate with ABMR occurrence. In multivariable Cox regression adjusted for desensitization treatment (AUC=0.810), only FCXM positivity (HR=4.6, p=0.001) and DSA number (HR=1.47, p=0.039) remained significant In conclusion, our data suggest pretransplant FCXM, DSA number but not DSA MFI are independent predictors of ABMR in patients who received peritransplant desensitization.